2020
DOI: 10.3389/fbioe.2020.00264
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Psoas Tendon Snapping. A Virtual Population Study

Abstract: Internal snapping of the psoas tendon is a frequently reported condition, especially in young adolescents involved in sports. It is defined as an increased tendon excursion over bony or soft tissue prominence causing local irritation and inflammation of the tendon leading to groin pain and often is accompanied by an audible snap. Due to the lack of detailed dynamic visualization means, the exact mechanism of the condition remains poorly understood and different theories have been postulated related to the etio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…It is composed by performing principal component analysis (PCA) of dense corresponding surface meshes obtained from 544 lower limb segmentations (362 male and 182 female training samples with an average age of 67.8 ± 10.8 and 69 ±13.3 years, respectively). The model was cleared from any positional variance (noise) that occurred at the time of image acquisition, therefore providing absolute standardization of hip positioning prior to morphometric analysis [ 32–36 ]. The imaging database on which the model is based was constructed from living subjects receiving angio-CT scanning for vascular work-out between 2012 and 2016.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is composed by performing principal component analysis (PCA) of dense corresponding surface meshes obtained from 544 lower limb segmentations (362 male and 182 female training samples with an average age of 67.8 ± 10.8 and 69 ±13.3 years, respectively). The model was cleared from any positional variance (noise) that occurred at the time of image acquisition, therefore providing absolute standardization of hip positioning prior to morphometric analysis [ 32–36 ]. The imaging database on which the model is based was constructed from living subjects receiving angio-CT scanning for vascular work-out between 2012 and 2016.…”
Section: Methodsmentioning
confidence: 99%
“…It was previously determined that 20 shape modes would largely sufficed to describe a sizable 99% of the total anatomical variance for both sexes [ 32 ]. We, therefore, retained t = 20 modes of variation to generate the virtual shapes, by randomly varying the normal distributed deviation weights b i within each point distribution model (Monte Carlo sampling).…”
Section: Methodsmentioning
confidence: 99%
“…The role of multiple iliopsoas tendon in ISHS remains an area of debate [16,17]. A study using dynamic sonography in 18 snapping hips suggested that this pathology could be due to the trapping of the iliopsoas tendon on the anterior surface of the iliacus muscle body and its abrupt collision with the pubic bone upon lateral release [1,4,6]. Additionally, they suggest that in a subset of patients, the snapping is the result of two separate iliacus tendon heads abruptly abutting one another.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome describes the painful and audible movement of the iliopsoas tendons across the hip joint, with the snapping thought to arise from movement over the iliopectineal eminence or the femoral head. Though the exact aetiology of this condition is not known, it has been speculated that anterior instability of the femoral head in the acetabulum with characteristic 3 o'clock anterior labral injury leads to tensioning of iliopsoas with resultant pain and snapping [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Using SSM, the authors generated a model of the lower limb to investigate psoas tendon behavior. [53] This revealed the exact location of psoas tendon movement and identified underlying torsional femoral dysplasia as an associated anatomic risk factor in snapping hip syndrome. If this is to be confirmed clinically, it will inform a change in surgical treatment from current practice.…”
Section: Stratification Of Diseasementioning
confidence: 91%